Women and essential oil usage: a literature review - Mazlan, Munirah; Mohamad Diah, Nurazzura (Penerbit Kolej Universiti Islam Melaka (KUIM), 2018)
Essential oil (EO) is a natural oil typically obtained through the process of distillation of plant and natural sources. Recently, the use of EOs has gained popularity, particularly among women as a result of renewed interest in the art of aromatherapy. In this paper, the researchers review the literature on EO usage across cultures in two ways: 1) describing the experience of using EOs and 2) defining factors that encourage women to use EOs. Searches of both social sciences and physical sciences databases were performed on relevant articles and empirical studies. Data from 30 articles were reviewed in this paper. The researchers conducted a summative content analysis to see variations in EO usage among women from different cultures. The study suggests that EO usage is common among women. EO is chosen to improve women’s physical and emotional wellbeing. It also shows considerable variations in outcome of EO usage like reducing agitation, relieving pain, improving sleep quality and mood, treating depression and also functioning as an antioxidant. Although this study found agreement among all cultures on the preference of using EOs, much of the evidence has put less emphasis on the importance of variables like different age group, racial/ethnic composition, social status, education and media exposure which explain women’s overall experience of using EOs. These socio-economic variations must also be taken into consideration. Finally, the study also indicates that researchers attempting cross-cultural studies need to holistically address in detail the social and cultural aspects surrounding EO usage. This paper also suggests for more interdisciplinary studies which will improve the understanding of this scenario in the future.